Initial use of combination treatment does not impact survival of 106 patients with haematologic malignancies and mucormycosis: a propensity score analysis. (September 2016) - Kyvernitakis, A.; Torres, H.A.; Jiang, Y.; Chamilos, G.; Lewis, R.E.; Kontoyiannis, D.P.
Abstract: In view of the poor outcomes associated with mucormycosis in patients with haematologic malignancies (HM) and haematopoietic cell transplant recipients, antifungal combinations are frequently used, yet the value of such strategy remains unclear. We reviewed the records of HM patients treated for mucormycosis from 1994 to 2014. The primary outcome was 6-week mortality after treatment initiation. Of the 106 patients identified, 44% received monotherapy and 56% received combination treatment as initial therapy. Six-week mortality was associated with disseminated mucormycosis (p 0.018), active malignancy (p <0.01), higher Acute Physiology and Chronic Health Evaluation (APACHE) II scores (p <0.001), neutropenia (p 0.049), lymphopenia (p 0.0003) and intensive care unit (ICU) admission at diagnosis (p 0.0001). Survivors were more likely to have localized mucormycosis (p <0.01) and to receive hyperbaric oxygen therapy (p 0.02). There were no differences in mortality between monotherapy and combination treatment groups (43% vs. 41%; p 0.85). In multivariate analysis, lymphopenia (odds ratio (OR), 5.5; 95% confidence interval (CI), 1.9–15.9; p 0.002) and ICU admission at diagnosis (OR, 8.2; 95% CI, 2.3–29.2; p 0.001) were associated with increased mortality. Localized mucormycosis was associated with better outcome (OR, 0.06; 95% CI, 0.01–0.6; p 0.019). Initial combination treatment had no impact on mortality, even after propensity score adjustment (OR, 0.8; 95% CI, 0.3–2.4; p 0.69). A weighted mortality risk score was then calculated for each patient based on the factors independently associated with mortality and baseline APACHE II score. In the low-risk group ( n  = 49), 13% of monotherapy versus 15% of combination therapy patients died within 6 weeks (p >0.99). In the high-risk group ( n  = 57), 71% of monotherapy versus 61% of combination therapy patients died within 6 weeks (p 0.42). With the current status of mucormycosis diagnosis, there was no difference in mortality in HM patients, whether they received monotherapy or combination treatment as initial therapy. Earlier diagnosis and immune reconstitution are unmet needs to affect outcomes.